Conducting Systematic Outcome Assessment in Private Addictions Treatment Settings - Gerard J Connors; Stephen A Maisto; Clare E Campbell; Brenda To; David Sack (SAGE Publishing, 2017)
Systematic outcome assessment is central to ascertaining the impact of treatment services and to informing future treatment initiatives. This project was designed to be conducted within the clinical operations of 4 private addictions treatment centers. A structured interview was used to assess patients' alcohol and other drug use and related variables (on treatment entry and at 1, 3, and 6 months following treatment discharge). The primary outcomes were percentage of days abstinent (PDA) from alcohol and drugs, PDA from alcohol, and PDA from other drugs. Collateral reports during follow-up also were gathered. A total of 280 patients (56% men) across the 4 programs participated. Percentage of days abstinent for each outcome increased significantly from baseline to the 1-month follow-up assessment, and this change was maintained at the 3- and 6-month follow-up assessments. Collateral reports mirrored the patient follow-up reports. Secondary outcomes of patient ratings of urges/cravings, depression, anxiety, and general life functioning all indicated significant improvement from baseline over the course of the follow-up. The results suggest the feasibility of conducting systematic outcome assessment in freestanding private addictions treatment environments.